Localized proton magnetic resonance spectroscopy of lipids in adipose tissue at high spatial resolution in mice in vivo - Klaus Strobel (Journal of Lipid Research, 2008)
We describe a localized proton magnetic resonance spectroscopy (1H-MRS) method for in vivo measurement of lipid composition in very small voxels (1.5 mm × 1.5 mm × 1.5 mm) in adipose tissue in mice. The method uses localized point-resolved spectroscopy to collect 1H spectra from voxels in intra-abdominal white adipose tissue (WAT) and brown adipose tissue (BAT) deposits. Nonlinear least-squares fits of the spectra in the frequency domain allow for accurate calculation of the relative amount of saturated, monounsaturated, and polyunsaturated fatty acids. All spectral data are corrected for spin-spin relaxation. The data show BAT of NMRI mice to be significantly different from BAT of NMRI nu/nu mice in all aspects except for the fraction of monounsaturated fatty acids (FM); for WAT, only the FM is different. BAT and WAT of NMRI mice differ in the amount of saturated and diunsaturated fatty acids. This method provides a potential tool for studying lipid metabolism in small animal models of disease during the initiation, progression, and manifestation of obesity-related disorders in vivo. Our results clearly demonstrate that localized 1H-MRS of adipose tissue in vivo is possible at high spatial resolution with voxel sizes down to 3.4 ml.